18.9k views
16 votes
Describe the zero product property and explain how tu use it to solve (2x + 10) (x - 7) = 0

User ThePeter
by
5.2k points

1 Answer

3 votes

Answer:

See below

Explanation:

Basically, when you have a product to two factors set equal to 0, you can use the Zero Product Property and make two separate equations, both set equal to 0, to find the roots for each factor:


2x+10=0\\2x=-10\\x=-5


x-7=0\\x=7

Notice that by plugging these roots back into the equation, either factor will be 0, making the whole expression 0:


(2x+10)(x-7)=0\\(2(7)+10)(7-7)=0\\(24)(0)=0\\0=0


(2x+10)(x-7)=0\\(2(-5)+10)(-5-7)=0\\(0)(-12)=0\\0=0

User Ftdysa
by
5.9k points